Learn Cocoa Touch for iOS - Kelley, Jeff (Apress : Imprint: Apress, 2012)
The Cocoa Touch frameworks and APIs are powerful tools for creating native iOS apps, and they're free with Xcode, Apple's development environment. If you've already gotten your feet wet with Objective-C, and you're ready to learn more about iOS development, then Learn Cocoa Touch for iOS is the book for you. You'll learn on the job - building cool apps as you read through the book that will teach you what you need to know to use Cocoa Touch and prepare you for creating your own apps. Learn Cocoa Touch for iOS shows you how to use frameworks like MapKit, Twitter, and MediaPlayer. You'll also learn about hardware APIs so you can get the most out of your accelerometer, camera, and more. You'll even learn about more advanced features like Grand Central Dispatch. A home inventory management system A live-updating Twitter client A photo browser with an animated slideshow  If you're ready for the next step toward becoming a Cocoa Touch master, this is the book for you.